A record of Cerapeplus Löbl & Burckhardt, 1988 (Coleoptera: Staphylinidae: Micropeplinae) in the Eastern Himalaya - Yin, Zi-Wei; Du, Jing-Zhe; Li, Li-Zhen (Zootaxa, 2026)
The genus Cerapeplus Löbl & Burckhardt, 1988 is reported to occur in the Eastern Himalaya. A new species, Cerapeplus luowaensis Yin, Du & Li sp. nov., is described and illustrated from Za’ri Valley of Lhünzê County, Xizang, China. The discovery brings the species number of this enigmatic lineage of Micropeplinae to three, and considerably expands the distributional range of the genus to the west.